METODE PERANCANGAN TEBAL PERKERASAN JALAN KAKU MENGGUNAKAN PEDOMAN PERENCANAAN PERKERASAN JALAN BETON SEMEN - Slamet Mardi Prastyanto; Muhammad Rendy (Politeknik Negeri Sriwijaya, 2024)
Roads have a very important role in life, including smoothing the flow of traffic, distribution of goods and services, as access to transportation between one region and another and can improve the economy in people's lives. In geometric and rigid pavement thickness design, there are basic references which include road class, horizontal alignment, vertical alignment and determination of pavement thickness. Based on the analysis and calculation of Pagar Alam City – Muara Pinang roads STA 22 + 750 – STA 28 + 650 belongs to the class IA arteri roads with a width of the road 3.5 x 2 m, and the shoulder of the road 1.5 x 2 m as well as using 8 curves is, 3 Full Circle curves, 3 Spiral-Circle-Spiral curves and 2 Spiral-Spiral curve. Pavement thickness design using a type of rigid pavement segmental construction without reinforcement by using joints and has a thick concrete plate of 21 cm (fc' 35 Mpa), aggregate foundation layer of 15 cm and stabilized base ground with a CBR of 6,8%. The construction of this road was carried out for 268 days with a total cost Rp87.533.871.173,- Keywords: Geometric Design, Rigid Pavement Thickness, Construction Cost Estimates